A New Host Factor Essential for Chikungunya Virus. Issue 1 (January 2020) - Schnierle, Barbara S.
Abstract : FHL1 has been identified as a host protein that is essential for chikungunya virus (CHIKV) replication. FHL1 interacts with the chikungunya non-structural protein 3, which is thought to recruit cellular proteins to the viral replication complex. Inhibition of this interaction is a promising target for drug development.